2020
DOI: 10.3390/w12041057
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Exopolymer Particle (TEPs) Dynamics and Contribution to Particulate Organic Carbon (POC) in Jaran Bay, Korea

Abstract: Transparent exopolymer particles (TEPs) are defined as acidic polysaccharide particles and they are influenced by various biotic and abiotic processes that play significant roles in marine biogeochemical cycles. However, little information on their monthly variation, relationship and contribution to particulate organic carbon (POC) is currently available particularly in coastal regions. In this study, the water samples were collected monthly to determine TEP concentrations and POC concentrations in a southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(106 reference statements)
2
5
1
Order By: Relevance
“…While weekly TEP measurements in this study were in the range of those previously made in estuarine systems (Morelle et al 2017;Ortega-Retuerta et al 2018;Lee et al 2020), we did not observe distinct trends in TEP concentration over the seasonal cycle. Other studies have noted seasonal TEP dynamics, with the highest TEP concentrations in the summer Fig.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…While weekly TEP measurements in this study were in the range of those previously made in estuarine systems (Morelle et al 2017;Ortega-Retuerta et al 2018;Lee et al 2020), we did not observe distinct trends in TEP concentration over the seasonal cycle. Other studies have noted seasonal TEP dynamics, with the highest TEP concentrations in the summer Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…Estuaries are carbon-rich areas of the ocean (Hopkinson and Smith 2005) and are highly dynamic, with significant daily and seasonal changes in environmental and biological gradients (Cloern and Jassby 2010). TEP has been shown to be an important contributor to carbon export within estuarine systems (Annane et al 2015;Morelle et al 2017;Lee et al 2020), with high TEP concentrations commonly found in the maximum turbidity zone (MTZ), areas where suspended particulate material accumulates (Malpezzi et al 2013). In addition, significant concentrations of TEP in estuaries could be derived from high inputs of terrestrial detrital material that is often partially remineralized by heterotrophic bacteria (Heip et al 1995).…”
Section: Communicated By Zhanfei Liumentioning
confidence: 99%
“…A correlation of TEP concentrations with the rise and decline of phytoplankton blooms is reported from lab cultures (Fukao et al, 2010), estuarine and nearshore areas (Bhaskar & Bhosle, 2006;Chowdhury et al, 2016;Ramaiah et al, 2001), and from the open ocean (Mari et al, 2017). Others report temporary disconnection of TEP from Chl-a concentrations (J. H. Lee et al, 2020;Ortega-Retuerta et al, 2018). Our data do not reveal any clear relationship between Chl-a and TEP concentration (see Figures 2j and 2l).…”
Section: Seasonal Variation In Tep Concentrationsupporting
confidence: 43%
“…To estimate TEP-C, we used the lowest conversion factor (0.51 µg Xeq. L −1 ) commonly used for the diatom-dominated phytoplankton community [51,102]. Considerably large variations in the contribution of TEP-C to the POC stocks were observed seasonally during our observation period (Figure 9), which was different from the seasonal pattern in the TEP concentrations.…”
Section: Seasonal Variations Of Tepsmentioning
confidence: 69%